Comparison Of The Historical Shoreline Changes Near AL- Kabeer Al-Shamali River Mouth for Pre And Post Construction Of 16 Tishreen Dam - AlAhmad, Reem (Latakia University Journal -Engineering Sciences Series, 2025)
Coasts are constantly changing areas due to several natural or human factors. The construction of dams on rivers is considered the most important human factor affecting changes in the shoreline near river mouths. Dams work to trap river sediments, which play an important role in nourishing the shoreline near the mouth. In this study, we use Digital shoreline analysis system (DSAS) to calculate changes in the shoreline near AL-Kabeer AL-Shamali river mouth before and after construction of 16 Tishreen dam on the river. This was done to determine impact of the dam construction on the changes. The results showed that AL-Rmel AL-Janoubi area coast was the most affected by construction of 16 Tishreen dam, with erosion rates increasing after the dam was built compared to before. As for AL-Bassa area coast, it experienced periods of both erosion and accretion after the dam was built, with minimal erosion rates before and after the dam construction.